Construction of a Standard Volume Table: A Case Study in Three Different Aged Teak Plantations in Bago Township, Bago Region, Myanmar - Naing, Yan Myo; Prasomsin, Patsi; Duangsathaporn, Khwanchai; Omule, Yenemurwon (วารสารวนศาสตร์ไทย, 2023)
In Myanmar, scientific research related to construction of a standard volume table that represents teak plantations in a specific area are rarely found, although it plays significant role in sustainable management of teak plantations. Therefore, in this study, a standard volume table was constructed, based on three teak plantations established in Bago Township by Forest Department (FD) of Myanmar. This is one area of eastern part of Bago Yoma Range known as “home of teak”. Ages of the plantations were 23, 27 and 31 years in 2013. Study methodology consisted of three main phases, namely, data collection, data preparation and, data analysis. In the first phase, the necessary data were collected using stratified random sampling technique. In the second phase, all the calculations needed for data analysis were prepared. In the last phase, data analysis was carried out to select the best volume model for construction of the standard volume table. Thirteen volume models were tested in this phase. Furnival’s Index (FI) was applied to compare all the models. The best fit volume model was V = - 0.0230361338 + 0.0000485831D2H - 0.0000008400D2H2 with the lowest FI of 0.0317. This model was used to construct a standard volume table of teak plantations in the study area. The developed volume table can be applied in the assessment of economic potential of standing teak trees in the study area. Therefore, this will lead to the achievement of the desired economic goal of the teak plantation management in Myanmar. Moreover, not only FD but also private sectors can effectively use the resultant volume equation and table in the prediction of growth and yield of teak plantations as a tool, particularly for the study area.